A Review of the Outcome of the Global Platform for Disaster Risk Reduction in 2019: An Azerbaijani Perspective - Huseynov, Yusif (International Journal of Economics and Financial Issues, 2019)
The main objectives of successful disaster risk reduction activities are the integration of risk reduction into national recovery programs, the development of policies and the progress of capacities designed to enhance and innovate preventive measures, awareness and risk assessment. This includes the analysis of threats and other vulnerabilities, as well as the development of knowledge, such as education, training of the population, in addition to emergency response protocols and the development of forecasting and early warning systems. A number of states have now become actively involved in the strengthening of their national capacities for disaster preparedness and risk reduction. Efforts are being made to ensure a systematic approach to identifying and assessing risks and minimizing the social and economic consequences of disasters. Therefore, the Global Platform’s contributions to states and to other stakeholders have been of significant importance. Countries such as the Republic of Azerbaijan are currently in the process of creating their own strategies concerning disaster risk reduction. It is also important to recognize the Global Platform for Disaster Risk Reduction in 2019 as a platform for viewing and analyzing the progress that the Republic of Azerbaijan has made on the Sendia Framework for Disaster Risk Reduction since 2015. Keywords: disaster risk reduction, Global Platform, Azerbaijan JEL Classifications: Q5, O2, I3, F5, R5 DOI: https://doi.org/10.32479/ijefi.8524